Sosialisasi Pestisida Nabati Ramah Lingkungan Di Desa Joho, Kabupaten Kediri - Anindita, Devina Cinantya; Sutiknjo, Tutut Dwi; Pawani, Rena Eksa (Kadiri University, 2023)
One of the problems the agricultural sector faces is the control of plant pest organisms (OPT). OPT control usually carried out by farmers is the use of chemical pesticides. Excessive use of chemical pesticides harms the environment. Environmentally friendly pest control efforts can be carried out by using vegetable pesticides. The use of botanical pesticides to control pest attacks still needs to be widely used by farmers. One effort to introduce plant-based pesticides is by carrying out outreach to introduce and manufacture environmentally friendly plant-based pesticides. The outreach was carried out directly with residents in Joho Village, Semen District, and Kediri Regency, and the practice of making vegetable pesticides was continued. The outreach was conducted to familiarize Joho Village residents with plants that can be used as essential ingredients for making vegetable pesticides. Plants used as pesticides can be taken from the roots, seeds, and leaves. Plants used as essential ingredients for vegetable pesticides include garlic, shallots, neem leaves, seeds, papaya leaves, roto wali, and various spices. The results of making vegetable pesticides will be distributed to residents in Joho Village, most of whom are farmers. Apart from that, plant seeds were also distributed to residents. The plant used as a botanical pesticide is garlic. This is because garlic contains allicin, tannin, saponin, and flavonoids. These compounds can cause a decrease in appetite in insects, inhibit molting, inhibit reproduction of female insects, cause larval death, suppress pupa formation, increase mortality, and disrupt insect metabolism. Garlic-based vegetable pesticides can be applied to horticultural crops such as chilies and eggplants. Through socialization, village residents understand how to make vegetable pesticides Salah satu permasalahan yang dihadapi oleh sektor pertanian adalah Pengendalian Organisme Pengganggu Tanaman (OPT). Pengendalian OPT yang biasa dilakukan oleh petani yaitu penggunaan pestisida kimia. Penggunaan pestisida kimia secara berlebihan memiliki dampak buruk bagi lingkungan. Upaya pengendalian OPT yang ramah lingkungan dapat dilakukan dengan menggunakan pestisida nabati. Penggunaan pestisida nabati untuk mengendalikan serangan OPT masih belum banyak digunakan oleh petani. Salah satu upaya pengenalan pestisida nabati yaitu dengan cara pelaksanaan sosialisasi pengenalan dan pembuatan pestisida nabati ramah lingkungan. Sosialisasi dilaksanakan secara langsung dengan warga di Desa Joho, Kecamatan Semen, Kabupaten Kediri dan dilanjutkan praktek pembuatan pestisida nabati. Sosialisasi dilakukan dengan tujuan agar warga Desa Joho lebih mengenal tumbuhan yang dapat dimanfaatkan sebagai bahan dasar pembuatan pestisida nabati. Tumbuhan yang digunakan sebagai pestisida dapat diambil dari bagian akar, biji dan daun. Tumbuhan yang dapat digunakan sebagai bahan dasar pestisida nabati antara lain: Bawang putih, bawang merah, daun dan biji mimba, daun papaya, rotowali dan berbagai rempah-rempah. Hasil pembuatan pestisida nabati akan dibagikan kepada warga di Desa Joho, yang sebagian besar adalah petani. Selain itu juga dibagikan bibit tanaman kepada warga setempat. Tumbuhan yang digunakan sebagai bahan pestisida nabati adalah bawang putih. Hal ini karena kandungan bawang putih yaitu, allicin, tannin, saponin dan flavonoid. Senyawan tersebut dapat mengakibatkan penurunan nafsu makan pada serangga, menghambat pergantian kulit, menghambat reproduksi serangga betina, menyebabkan kematian larva, menekan pembentukan pupa, meningkatkan mortalitas, serta menggangu metabolisme serangga. Pestisida nabati berbahan dasar bawang putih dapat diaplikasi pada tanaman hortikultura seperti cabai dan terong. Melalui sosialisasi warga desa memahami pembuatan pestisida nabati